'Embodiments of the invention': Patents and urban diagrammatics in the smart city. (August 2020) - Shapiro, Aaron
How do technology firms compete to colonize the urban future? This article theorizes technology patents as a medium of urban futuring. Patents secure legal exclusion by disclosing an idea or invention. However, the incentive structures behind patents are ambiguous. Patent holders must articulate inventions with enough technical specificity to warrant a property claim while remaining strategically imprecise enough to capture unanticipated future uses. I build on the Foucaultian theory of the diagram to discuss patents' interplay of disclosure and secrecy as a strategic anticipatory practice for colonizing urban futures. Whereas modern urban governance operated on spatial form to discipline citizens, smart city technology patents reflect a splintering of technical capacity and control. In the empirical section, I analyze three patent-diagrams: the first for a Wi-Fi-enabled advertising system, the second for a notification system for autonomous vehicles, and the third for an algorithmic predictive policing platform. These examples show that at a fundamental level, smart city technologies are less discrete inventions than claims to the capacity to influence human–machinic interactions. The article concludes with a reflection on how critical urbanists can learn from technology patents to advance more democratic and publicly oriented visions for the city.